Experiences of Being a Mother: Meanings of Childbirth, Pain and Birth - Coutinho, Emília de Carvalho; Silva, Alcione Leite da; Pereira, Carlos Manuel Figueiredo; Rouxinol, Diana Filipa Chaves; Parreira, Vitória Barros Castro; Nelas, Paula Alexandra Batista; Chaves, Cláudia Margarida Balula; Cabral, Lídia do Rosário (Fronteira: Journal of Social, Technological and Environmental Science, 2014)
The experiences of delivery and birth profoundly shape the lives of women, couple and family. The objective of this study is to understand the meanings attributed to childbirth, pain and birth, by Portuguese and immigrant women in Portugal, and identify the meanings and feelings experienced by the woman who becomes a mother. It is a qualitative study, resorting to semi-structured interviews and content analysis, to 60 immigrant and 22 Portuguese women, supported by Nvivo10. The results suggest that the meanings of childbirth, labour pains, and birth are diverse and ambivalent, according to the experience of each woman. Labour pains presented disparate meanings between being horrible or necessary, but rewarding... Keywords: Experiences; Labour; Pain; Birth.